Site localization of Cd impurities in sapphire - Darriba, Germán Nicolás (2012)
By combining first-principles electronic structure calculations and existing time-differential γ-γ perturbed-angular-correlation experiments we studied the site localization, the local environment, and the electronic structure of Cd impurities in sapphire (α-Al2O3) single crystals in different charged states. The ab initio calculations were performed with the full-potential augmented plane wave plus local orbitals method and the projector augmented wave method. Comparing the calculated electric-field-gradient tensor at the Cd nuclei in the α-Al2O3 host lattice and the corresponding available experimental values, we have seen that it is equally possible for Cd to replace an Al atom (in a negative charge state) or to be placed in an interstitial site (in a neutral charge state). To finally address the issue of the Cd impurity localization, we performed formation energy calculations. These results have shown that Cd placed in the substitutional Al site, in the negatively charged state, is the most probable configuration.